The Mediating Effect of Self-Efficacy on the Clinical Learning Environment and Critical Thinking - Gangoso, Shaniah; Ihimbazwe, Aline; Rey, Kristel Anne M.; Jael, Susy A.; Mergal, Beryl Ben; Falculan, Raymund M.; Orbe, Joyosthie B. (8ISC Proceedings: Arts and Education, 2022)
Newly graduated nursing students entering the work field are not meeting the standard levels of skills such as critical thinking. The clinical learning environment (CLE) is a crucial part of nursing education that allows nursing students to develop critical thinking skills while dealing with real-life patient scenarios. Moreover, present during clinical exposure is self-efficacy that is vaguely linked to the CLE and critical thinking. Hence, this study aims to identify the relationships between these three variables. This quantitative study purposively sampled 134 nursing students enrolled during the Academic Year 2019-2020. Respondents answered an online survey questionnaire composed of four parts: the demographic profile, CLE, perceived clinical self-efficacy, and critical thinking. The descriptive statistics using SPSS 24 revealed that the respondents perceived their CLE as good, they had a high level of perceived clinical self-efficacy, and they had a good level of perceived critical thinking. Moreover, Structural Equation Modeling (SEM) using AMOS 23 revealed that the model’s fit indices are excellent (CMIN = .985; CFI = 1; SRMR = 0.043; RMSEA = 0.00; and PClose = 0.895). Analysis showed that CLE has a positive direct effect on perceived clinical self-efficacy but no significant direct effect on perceived critical thinking. Further, perceived clinical self-efficacy has a positive direct effect on perceived critical thinking. Lastly, self-efficacy fully mediates the positive relationship between the CLE and perceived critical thinking. Evidence reveals that nursing educators could increase students’ perceived critical thinking in the clinical area by enhancing self-efficacy. The study recommends replication of the study with larger samples and that CLE instruments should be further validated and developed. Keywords : self-efficacy, hospital placement, structural equation modeling, critical thinking